1999
DOI: 10.1007/s002140050511
|View full text |Cite
|
Sign up to set email alerts
|

Bis-periazulene: a simple Kekul� biradical with a triplet ground state

Abstract: B3LYP/6-31G* calculations on bis-periazulene (cyclohepta[def ]-¯uorene) predict a triplet ground state for this molecule. The singlet has an aromatic 14pelectron periphery but is 2 kcal/mol higher in energy. The results agree with earlier predictions by Heilbronner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
(10 reference statements)
0
17
0
Order By: Relevance
“…The only unsynthesized isomer, bis-periazulene (cyclohepta­[ def ]­fluorene) 1 , remains elusive despite many synthetic efforts. The first synthetic attempt for 1a was reported in 1955 by Reid .…”
mentioning
confidence: 99%
“…The only unsynthesized isomer, bis-periazulene (cyclohepta­[ def ]­fluorene) 1 , remains elusive despite many synthetic efforts. The first synthetic attempt for 1a was reported in 1955 by Reid .…”
mentioning
confidence: 99%
“…Furthermore, Konishi and Yasuda et al. synthesized a bis‐periazulene (cyclohepta[ def ]fluorene) derivative 5 , [19] whose ground state was calculated to be triplet, [20] but experimentally elucidated as singlet with a small singlet‐triplet energy gap (Δ E ST ) of −3.78 kJ mol −1 . Similarly, Ma, Bogani, and Feng et al.…”
Section: Figurementioning
confidence: 99%
“…In addition, Haley et al synthesized an indeno[1,2-a]fluorene derivative 4, [18] whose ground state was not experimentally confirmed due to the insufficient ESR measurement at low temperatures. Furthermore, Konishi and Yasuda et al synthesized a bis-periazulene (cyclohepta[def]fluorene) de- rivative 5, [19] whose ground state was calculated to be triplet, [20] but experimentally elucidated as singlet with a small singlet-triplet energy gap (ΔE ST ) of À 3.78 kJ mol À 1 . Similarly, Ma, Bogani, and Feng et al reported the synthesis of benzo-fused cyclohepta[def]fluorenes possessing a singlet ground state with a very low-lying triplet excited state.…”
mentioning
confidence: 99%
“…These systems all have quinoidal core structures derived conceptually by linking simple radical-containing units through one or more p -phenylenes or thiophenes, by linking delocalized phenalenyl radicals via an aromatic core, or by incorporation of the same basic design features into more complex π-frameworks. , In one case a thermally accessible quintet state of a quinoidal dinitrene was observed . Triplet ground states in neutral biradicaloid species have been predicted on the basis of PPP calculations, and more recently based on density functional calculations for acenes, cyclacenes, and derivatives, bisperiazulene, , an oligoazulene, and large fluoranthene-based hydrocarbons. , To date, only one such biradicaloid, 1 ( n = 2), has been demonstrated experimentally to have a triplet ground state. , …”
Section: Introductionmentioning
confidence: 99%
“…28,29 In one case a thermally accessible quintet state of a quinoidal dinitrene was observed. 30 Triplet ground states in neutral biradicaloid species have been predicted on the basis of PPP calculations, 31−34 and more recently based on density functional calculations for acenes, cyclacenes, and derivatives, 35−37 bisperiazulene, 38,39 an oligoazulene, 40 and large fluoranthene-based hydrocarbons. 41,42 To date, only one such biradicaloid, 1 (n = 2), has been demonstrated experimentally to have a triplet ground state.…”
Section: ■ Introductionmentioning
confidence: 99%